The Development of a Blended Supervision Model to Promote Active Learning Based on the School as Learning Community Concept to Enhance Students’ Quality in World-Class Standard Schools - Tanchai, Sathaka (Journal for Developing the Social and Community, 2026)
Background and Aims: Particularly at World-Class Standard Schools that prioritize active learning and 21st-century skills, educational supervision is essential to improving teacher quality and student learning results. However, the burden of instructors, time limits, and a lack of integration with school development goals are some of the drawbacks that conventional monitoring systems frequently confront. As a result, under the idea of the School as a Learning Community (SLC), a novel supervision model that combines technology with collaborative learning principles is required. This study aimed to (1) examine the current state, desirable state, and priority needs of educational supervision, (2) develop a blended supervision model to promote active learning based on the School as Learning Community concept, (3) investigate the effects of implementing the model, and (4) evaluate and expand the developed model in World-Class Standard Schools under the Roi Et Secondary Educational Service Area Office. Methodology: This research employed a Research and Development (R&D) design conducted in four phases. The sample in the implementation phase consisted of 66 administrators and teachers from 7 World-Class Standard Schools, as well as 420 students. Research instruments included questionnaires, interview forms, and evaluation forms. Quantitative data were analyzed using mean, standard deviation, and the Modified Priority Needs Index (PNImodified), while qualitative data were analyzed through content analysis. Results: The results showed that all parts of the desired state of supervision were better than the present state, with problem identification and needs assessment having the greatest priority. The created blended supervisory model, called the SO Model, had six supervision approaches and a 10-step supervision process. It incorporated three aspects (Agenda-Based, Function-Based, and Area-Based supervisory). According to World-Class Standard criteria, teachers’ active learning competencies and school quality were at the highest level, according to implementation outcomes. High levels of utility, feasibility, propriety, and correctness were found in the model evaluation, and it was effectively extended to additional schools. Conclusion: The blended supervision model developed in this study significantly improved teachers’ active learning competencies and school quality, in keeping with the goals of World-Class Standard Schools. The SO Model has a lot of potential as a long-lasting and adaptable supervisory framework that promotes continuous educational progress and a collaborative learning culture.